On the 2-primary Part of Tame Kernels of Real Quadratic Fields - Cheng, Xiao Yun; Guo, Xue Jun (Acta mathematica Sinica. English series, 2016)
Let F = Q（x/P）, where p = 8t ＋ 1 is a prime. In this paper, we prove that a speclm case of Qin＇s conjecture on the possible structure of the 2-primary part of K2OF up to 8-rank is a consequence of a conjecture of Cohen and Lagarias on the existence of governing fields. We also characterize the 16-rank of K2OF, which is either 0 or 1, in terms of a certain equation between 2-adic Hilbert symbols being satisfied or not.